Introduction: The Journal of Transport and Land Use enters year four - Levinson, David M (Journal of Transport and Land Use, 2011)
The Journal of Transport and Land Use enters its fourth year with this issue. We are pleased to see how far it has come. As an open access journal, we are doing something that remains in some ways experimental, but in others quite proven. Our readership is large and growing, in one year (December 1, 2009 to December 1, 2010) we had 11,759 visits from 7,714 visitors, coming from 119 countries. While the plurality are from the US, it is not a majority. Other large readerships come from the United Kingdom, Canada, India, the Netherlands, Italy, Australia, China, Indonesia, and Japan. In three years (through Fall 2010) we had 231 submissions and 37 published articles (excluding 15 book reviews, issue introductions, discussions, etc.). Our acceptance rate is 28 percent. We are indexed in Google Scholar and Research Papers in Economics (RePEc), and have applied to other online indexing services, though these take time. According to Google Scholar, JTLU articles have been cited over 184 times, or 3.53 citations per item, with an H-index of 6 (6 articles cited 6 or more times).